Identification of Bone Marrow Cell Subpopulations Associated with Improved Functional Outcomes in Patients with Chronic Left Ventricular Dysfunction: An Embedded Cohort Evaluation of the FOCUS-CCTRN Trial. Issue 9 (September 2016) - Taylor, Doris A.; Perin, Emerson C.; Willerson, James T.; Zierold, Claudia; Resende, Micheline; Carlson, Marjorie; Nestor, Belinda; Wise, Elizabeth; Orozco, Aaron; Pepine, Carl J.; Henry, Timothy D.; Ellis, Stephen G.; et al.
In the current study, we sought to identify bone marrow-derived mononuclear cell (BM-MNC) subpopulations associated with a combined improvement in left ventricular ejection fraction (LVEF), left ventricular end-systolic volume (LVESV), and maximal oxygen consumption (VO2 max) in patients with chronic ischemic cardiomyopathy 6 months after receiving transendocardial injections of autologous BM-MNCs or placebo. For this prospectively planned analysis, we conducted an embedded cohort study comprising 78 patients from the FOCUS-Cardiovascular Cell Therapy Research Network (CCTRN) trial. Baseline BM-MNC immunophenotypes and progenitor cell activity were determined by flow cytometry and colony-forming assays, respectively. Previously stable patients who demonstrated improvement in LVEF, LVESV, and VO2 max during the 6-month course of the FOCUS-CCTRN study (group 1, n = 17) were compared to those who showed no change or worsened in one to three of these endpoints (group 2, n = 61) and to a subset of patients from group 2 who declined in all three functional endpoints (group 2A, n = 11). Group 1 had higher frequencies of B-cell and CXCR4 + BM-MNC subpopulations at study baseline than group 2 or 2A. Furthermore, patients in group 1 had fewer endothelial colony-forming cells and monocytes/macrophages in their bone marrow than those in group 2A. To our knowledge, this is the first study to show that in patients with ischemic cardiomyopathy, certain bone marrow-derived cell subsets are associated with improvement in LVEF, LVESV, and VO2 max at 6 months. These results suggest that the presence of both progenitor and immune cell populations in the bone marrow may influence the natural history of chronic ischemic cardiomyopathy—even in stable patients. Thus, it may be important to consider the bone marrow composition and associated regenerative capacity of patients when assigning them to treatment groups and evaluating the results of cell therapy trials.